Whole-Exome Sequencing Enables the Diagnosis of Variant-Type Xeroderma Pigmentosum - Fang, Xiaokai; Sun, Yonghu (Frontiers in Genetics, 2019)
Abstract Background: Xeroderma pigmentosum (XP) is a rare autosomal, recessive, inherited disease. XP patients exhibit high sensitivity to sunlight and increased incidence of skin cancer. The different XP subtypes, which are caused by mutations of 8 distinct genes, show some specific clinical manifestations. XP variant (XPV) is caused by mutations in the gene encoding DNA polymerase eta (POLH). Case Presentation: We report a family that included 2 XP patients whose parents were first cousins. The proband is a 36-year-old male who developed a large number of pigmented freckle-like lesions starting at 4 years of age; later, he displayed typical psoriasis manifestation, abnormal renal function and hyperglycaemia. He was suspected as suffering from dyschromatosis symmetrica hereditaria (DSH), but negative results were obtained in candidate gene analyses. Whole-exome sequencing was performed in 4 subjects, including the two patients and two controls, and a new pathogenic homozygous nonsense mutation (c.353dupA, p. Y118_V119delinsX) of the POLH gene, which was identified in all 9 family members by Sanger sequencing, was detected in the patients. Conclusions: A novel XPV pathogenic homozygous nonsense mutation in the POLH gene was identified. Our case proves that next-generation sequencing is an effective method for the rapid diagnosis and determination of XP genetic aetiology.